An Analysis of the Commonality and Type of Preintervention Assessment Procedures in the Journal of Organizational Behavior Management (2000–2015). Issue 1 (2nd January 2018) - Wilder, David A.; Lipschultz, Joshua L.; King, Allison; Driscoll, Sean; Sigurdsson, Sigurdur
ABSTRACT: We reviewed all issues of the Journal of Organizational Behavior Management ( JOBM ) from 2000 through 2015 to identify the percentage of empirical articles, which utilized some form of preintervention assessment. In addition, we categorized five types of assessment used and compared the number of assessments conducted in each category. Finally, because assessment is considered to be particularly important in the subdiscipline of behavioral safety (McSween, 2003), and prior research has not examined the commonality of assessment in this area, we also analyzed the frequency and type of assessment procedures used in behavioral safety and compared this to the use of assessment in OBM in general. Results indicated that 28% of the empirical articles in JOBM used some form of preintervention assessment. Indirect methods were the most often used type of assessment. In addition, 48% percent of the articles in JOBM, which employed a safety-related dependent variable, included some form of assessment. The most frequently used type of assessment in behavioral safety was historical assessment. Based on these data, the use of some form of preintervention assessment in OBM appears to be occurring with some regularity, and assessment in behavioral safety is more common relative to assessment in OBM in general.